Pengaruh Penggunaan Media Peta dalam Meningkatkan Hasil Belajar Kognitif Siswa di SDN Negri 1 Mendana: The Effect of Using Map Media in Improving Students' Cognitive Learning Outcomes at SDN Negri 1 Mendana - Lalu. A. Hery Qusyairi (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
Media can be used to simplify or facilitate learning for students in abstract subjects. Media is also believed to help teachers simplify and overcome communication problems they encounter when teaching a given topic. This study aims to determine the effect of using map media in improving students' cognitive learning outcomes at SDN Negri 1 Mendana. This type of research uses a quantitative approach. This quantitative approach is an approach that describes or illustrates a problem or event using numbers or results in non-descriptive form. The results of the study found that the application of map media in improving students' cognitive learning outcomes at SDN Negri 1 Mendana experienced the expected increase. Maps are a perfect medium for enhancing student knowledge. Of the 20 samples used in the study, approximately 55% of maps significantly impacted student knowledge.